Structure-Seabed Interactions in Marine Environments - Jeng, Dong-Sheng; Guo, Zhen; Hong, Yi (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
The phenomenon of soil-structure interactions in marine environments has attracted great attention from coastal geotechnical engineers in recent years. One of the reasons for the growing interest is the rapid development of marine resources (such as in the oil and gas industry, marine renewable energy, and fish farming industry) as well as the damage to marine infrastructure that has occurred in the last two decades. To assist practical engineers in the design and planning of coastal geotechnical projects, a better understanding of the mechanisms of soil-structure interactions in marine environments is desired. This Special Issue reports the recent advances in the problems of structure-seabed interactions in marine environment and provides practical engineers and researchers with information on recent developments in this field.